Leadership Behavior as a Health-Promoting Resource for Workers in Low-Skilled Jobs and the Moderating Role of Power Distance Orientation. (February 2014) - Winkler, Eva; Busch, Christine; Clasen, Julia; Vowinkel, Julia
In this study, the authors analyze leadership behaviors as potential health-promoting resources for low-skilled workers in a highly culturally diverse work setting. The authors hypothesize that subordinates' and supervisors' individual power distance orientations will moderate the effect of subordinates' perceptions of leadership behavior and the subsequent effects on their well-being. Multilevel modeling is used to analyze a sample of data from 474 low-skilled employees (50% immigrants) and 35 direct supervisors from three German companies. Supporting the hypotheses, social support, task-related communication, and positive feedback, as expressions of esteem, are found to positively impact subordinates' well-being, but individual consideration shows no significant effects. Furthermore, results confirm that supervisors' power distance orientation moderates employees' perceptions about supervisors' positive feedback and the subsequent well-being effects. The moderating effect fails to hold for employees' power distance orientation. Results indicate that supervisors can most effectively promote the health of low-skilled workers by showing esteem through positive feedback, but if the supervisor has high individual power distance orientation, the effect is attenuated.